The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1259/bjr.20210533
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and efficacy of stereotactic body radiotherapy for ultra-central lung tumours: a single institution real life experience

Abstract: Objectives: The use of stereotactic body radiotherapy (SBRT) to treat ultra-central lung tumours remains more controversial than for peripheral and central tumours. Our objective was to assess toxicities, local control (LC) rate and survival data in patients with ultra-central lung tumours treated with SBRT. Methods: We conducted a retrospective and monocentric study about 74 patients with an ultra-central lung tumour, consecutively treated between 2012 and 2018. Ultra-central tumours were defined as tumours w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
1
6
2
Order By: Relevance
“…To our knowledge, most of the published studies investigating only ultra-central lung tumors analyzed the high-risk indicators for treatment-related mortality or local control, excluding clinical factors significantly associated with better OS or PFS, except for the study of Breen et al [ 21 ]. Interestingly, unlike previous literature [ 17 , 19 , 30 ], this study identified female gender, age < 70 years, and tumor-trachea distance ≤ 5 mm as independent prognostic factors associated with better OS. Moreover, patients with a tumor size < 5 cm were significantly associated with better OS as compared to patients with a tumor size ≥ 5 cm.…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…To our knowledge, most of the published studies investigating only ultra-central lung tumors analyzed the high-risk indicators for treatment-related mortality or local control, excluding clinical factors significantly associated with better OS or PFS, except for the study of Breen et al [ 21 ]. Interestingly, unlike previous literature [ 17 , 19 , 30 ], this study identified female gender, age < 70 years, and tumor-trachea distance ≤ 5 mm as independent prognostic factors associated with better OS. Moreover, patients with a tumor size < 5 cm were significantly associated with better OS as compared to patients with a tumor size ≥ 5 cm.…”
Section: Discussioncontrasting
confidence: 91%
“…Similar results were reported by Breen et al [ 21 ] and Lodeweges et al [ 19 ], with 1-year and 2-year OS rates of 78% and 57%, and 77% and 52%, respectively. One-year LC was 97% in the study reported by Guillaume et al [ 17 ], and 98% in the work by Lodeweges et al [ 19 ], slightly higher than our findings. Across the studies investigating SBRT for ultra-central tumors, there was a significant heterogeneity in terms of fractionation schedules.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…29 For organizational reasons, IGTA is preferred over SBRT at our institution except for ultracentral PM, contraindicated for IGTA and which would require extensive lung resection. 30 Groups were not comparable per se as indications were different, but similar results were observed after PSM analysis nonetheless. It is likely that length of stay would decrease after surgery while implementing enhanced recovery strategies.…”
Section: Discussionmentioning
confidence: 68%